APLIKASI PEMESANAN RENTAL MOBIL PADA ISTIQOMAH RENT CAR CILEGON BERBASIS WEB - Dedi Juniansha; Waliadi Gunawan (Journal of Innovation And Future Technology (IFTECH), 2022)
Car rent is a business entity in the field of four-wheeled rental services (car). the Application Booking Car at Istiqomah Rent Car Cilegon. not yet effective because every data of borrowing, returning, and other daily transactions with its report is still manually written on papers and books, so that the system the not efficient in saving time, energy and materials. This research is made to know current running system, making the system design, and to know the implementation of the system design made. This research is intended to make the web based car rental Application Booking Car at Istiqomah Rent Car Cilegon. The results from studies in Istiqomah Rent Car Cilegon can be concluded that with the construction of the application booking of borrowing and return of cars is expected to assist employees to organite customer’s data, borrowing, repayment and can reduce errors in data recording process and reduce errors in reporting. The methodology used in making this Final Project is to use the Waterfall methodology consisting of the stages of Requirement Analysis, System Design, Coding, Program Testers, Maintenance, while the programming language used is php programming language and for its database using MySql.